2022
DOI: 10.1123/jab.2022-0088
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Achilles Tendon Rupture in National Basketball Association Players

Abstract: A systematic search was performed of online databases for any Achilles tendon (AT) injuries occurring within the National Basketball Association (NBA). Video was obtained of injuries occurring during competition and downloaded for analysis in Dartfish. NBA athletes (n = 27) were identified with AT rupture over a 30-year period (1991–2021). Of the 27 NBA athletes found to have AT ruptures (mean age: 29.3 [3.3] y; average time in the NBA: 8.5 [3.8] y), 15 in-game videos were obtained for analysis. Noncontact rup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
(59 reference statements)
1
2
1
Order By: Relevance
“…Only 23.7% of the injuries examined were non-contact. This is a significantly lower prevalence than multiple other studies,16 17 37 38 but similar to a recent study on NBA athletes 18. This lower prevalence could be due to different definitions of ‘contact’ between studies.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Only 23.7% of the injuries examined were non-contact. This is a significantly lower prevalence than multiple other studies,16 17 37 38 but similar to a recent study on NBA athletes 18. This lower prevalence could be due to different definitions of ‘contact’ between studies.…”
Section: Discussionsupporting
confidence: 81%
“…That could potentially be attributed to differences in video quality, and to the fact that their study did not quantifiably measure biomechanical angles using formal tools. A more recent study on NBA athletes identified IC knee flexion angle to be slightly greater than this study (21.3° vs 12.6°) 18. However, that study measured some kinematics at the time of whole foot ground contact, rather than any ground contact like this study.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations